(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This study investigates the effectiveness of using educational applications to enhance English language skills among high school students. With the rapid advancement of educational technology, the role of digital tools in language learning is increasingly significant. The research focuses on how applications such as Duolingo, Grammarly, Quizlet, Kahoot, Memrise and BBC Learning English support the development of reading, writing, listening, and speaking skills. These tools were integrated into classroom instruction based on structured lesson plans, and after each session, students’ participation, comprehension levels, and assessment results were analyzed. The findings indicate that Duolingo was particularly effective in vocabulary acquisition and lexical exercises. Grammarly served as a valuable resource for checking written work, analyzing errors, and reinforcing grammar knowledge. BBC Learning English demonstrated high efficacy in listening comprehension activities. Besides, the use of these digital tools enhanced student engagement and fostered independent learning. The interactive and engaging nature of the applications allowed students to practice meaningfully and autonomously. The study also measured changes in students’ motivation and performance before and after the implementation of these tools. Results suggest that integrating such technologies in English language classrooms not only increases motivation but also boosts students’ confidence and interest in the subject. This research underscores the significance of modern teaching strategies in developing essential 21st-century communication skills.